2022
DOI: 10.3389/fbioe.2022.997877
|View full text |Cite
|
Sign up to set email alerts
|

Cervical subtotal discectomy prosthesis validated in non-human primate model: A novel artificial cervical disc replacement concept?

Abstract: Objective: To evaluate the biological function of cervical subtotal discectomy prosthesis (CSDP) implantation in a non-human primate model.Methods: A CSDP was tested for cytocompatibility and osseointegration capacity before implantation in non-human primates. Subsequently, the CSDP was improved based on three-dimensional CT measurements of the non-human primate cervical spine. Eight cynomolgus monkeys were selected for removal of the intervertebral disc and lower endplate of the C5/6 segment to complete the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…While macaques are currently the primary experimental animal donor, with up to 94% genetic homology with humans [24][25][26] , and have been an ideal subject for non-human primate experiments in many elds of scienti c research such as brain science, psychology, behavior, and medicine [27][28] . Liu and other scholars [29] established cervical subtotal discectomy prosthesis (CSDP) implantation in a non-human primate model. They demonstrated that CSDP has excellent safety and biomechanical stability and would provide a new option for treating cervical disc disease.…”
Section: Discussionmentioning
confidence: 99%
“…While macaques are currently the primary experimental animal donor, with up to 94% genetic homology with humans [24][25][26] , and have been an ideal subject for non-human primate experiments in many elds of scienti c research such as brain science, psychology, behavior, and medicine [27][28] . Liu and other scholars [29] established cervical subtotal discectomy prosthesis (CSDP) implantation in a non-human primate model. They demonstrated that CSDP has excellent safety and biomechanical stability and would provide a new option for treating cervical disc disease.…”
Section: Discussionmentioning
confidence: 99%